Probable awake bruxism - prevalence and associated factors: a cross-sectional study - Priscila Brenner HILGENBERG-SYDNEY; Ana Laura LORENZON; Giovanna PIMENTEL; Ricardo Rasmussen PETTERLE; Daniel BONOTTO (Dental Press Editora, 2022)
ABSTRACT Introduction: Bruxism is defined as a repetitive activity of masticatory muscles, characterized by the clenching or grinding of the teeth, which can occur during wakefulness (awake bruxism) or during sleep (sleep bruxism). Objectives: The objectives of the present study were to determine the prevalence of awake bruxism and its associated factors. Methods: Sample was composed by 50 participants of both genders, aged between 18 and 60 years, submitted to a clinical examination - to observe the presence of tooth wear, marks on the mucosa, or masseter muscles hypertrophy - and self-applied questionnaires, which evaluated the presence of TMD signs and symptoms, oral behaviors, lifestyles, anxiety level and sleep quality. Results: The prevalence of awake bruxism was 48%. Its presence was statistically and significantly associated with the presence of signs and symptoms of TMD (p=0.002), poor sleep quality (p=0.032), buccal mucosa indentations (p<0.001) and tongue (p=0.011). Age, gender, social characteristics, habits (such as coffee ingestion, smoking, alcoholism and physical activity) and tooth wear were variables that had no significant association with awake bruxism. Conclusions: It was concluded that awake bruxism shows a high prevalence and a positive association with signs and symptoms of TMD and worst sleep quality. In addition, awake bruxism is more likely to occur in individuals who have buccal mucosa indentation and who present high rates of oral habits and oral behaviors.